Posttraumatic growth and parental bonding in young adults of parents with physical disabilites: testing mediation model of resilience. Issue 6 (3rd July 2018) - Li, Yuli; Xing, Aihong; Chen, Xiaoyun; Lou, Fenglan; Cao, Fenglin
Abstract: Positive parent-child relationships are associated with positive youth development, but little is known about the relationships between parental bonding, resilience, and posttraumatic growth, which is positive change resulting from the struggle with trauma. This study examined a mediation model among 119 female young adults with disabled parents. The model included resilience as a mediator of the relationship between the paternal Care and posttraumatic growth. The results revealed that resilience did mediate the relationship between the paternal Care and posttraumatic growth. The findings indicate that paternal Care helps to foster female young adults' resilience, which benefits their growth after suffering adversities.